Performance and style of play after returning from concussion in the National Hockey League - Kuhn, A. W.; Zuckerman, S. L.; Totten, D.; Solomon, G. S. (The American Journal of Sports Medicine, 2016)
Background: Few studies have empirically examined outcomes of concussion in the National Hockey League (NHL) and whether these athletes return to games after concussion at a performance level comparable to preconcussion play. Hypothesis: NHL players would not demonstrate changes in performance or style of play after returning from a concussion when compared with a group of control athletes. Study Desig : Cohort study; Level of evidence, 3. Methods: NHL players with a reported hockey-related concussion during the 2008-2009 through 2014-2015 seasons were identified utilizing secondary media sources. Players who missed games for non-injury related causes were selected as the control group. "Performance" was operationally defined as the statistics for goals, assists, points, plus-minus, and shots, and "style of play" was operationally defined as the statistics for penalty minutes, blocked shots, hits, giveaways, and time on ice. Each gameplay statistic was recorded and totaled for the 5 games before and after each player's injury or absence. After meeting strict inclusion criteria, the 2 groups were compared across each postconcussion/absence statistic by generalized linear models while incorporating the particular preconcussion/absence statistic, position played, games missed, and concussion history as covariates to control for intraplayer and between-group differences. Results: A total of 287 players sustained a concussion; 130 missed time for non-injury related reasons and were identified as controls. After the exclusion criteria were applied, 94 concussed players were compared with 58 controls. None of the models reached statistical significance, indicating that the concussion and control groups did not differ across performance or style of play after returning from a concussion or non-injury related absence. Conclusions: